2017
DOI: 10.1186/s13075-017-1292-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural predictors of response to intra-articular steroid injection in symptomatic knee osteoarthritis

Abstract: BackgroundThe aim was to examine if structural factors could affect response to intra-articular steroid injections (IASI) in knee osteoarthritis (OA).MethodPersons with painful knee OA participated in an open-label trial of IASI where radiographic joint space narrowing (JSN) and Kellgren-Lawrence (KL) grade, whole-organ magnetic resonance imaging (MRI) scores (WORMS) and quantitative assessment of synovial tissue volume (STV) were assessed on baseline images. Participants completed the Knee Injury and Osteoart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…There are few data concerning the impact of psychological factors on treatment response 7 . In our recent open-label study of IASI in knee OA 14,15 , not all participants responded to the therapy in the short-term. Of those who responded, the majority had a recurrence of pain within 6-months.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…There are few data concerning the impact of psychological factors on treatment response 7 . In our recent open-label study of IASI in knee OA 14,15 , not all participants responded to the therapy in the short-term. Of those who responded, the majority had a recurrence of pain within 6-months.…”
mentioning
confidence: 90%
“…Of those who responded, the majority had a recurrence of pain within 6-months. In previous work, we looked at the impact of disease severity on outcome following IASI and found that those with more severe disease[either magnetic resonance imaging(MRI) or x-ray] were less likely to be longer-term responders 14,15 . The aim of the current study was to determine the impact of a range of clinical correlates of disease including symptoms, clinical signs of knee OA, psychologic factors and quality of life, on both short-term(within 2-weeks) and longer-term(6-months) outcome following IASI.…”
mentioning
confidence: 99%
“…Associations for linear regression models are presented as standardized regression coefficients (b). Estimates are presented from crude models, and from fully adjusted models which accounted for other predictors shown here or in previous studies to be associated with knee pain persistence (including age, sex, BMI, radiographic OA, and symptom duration) 3,4,12 . Spearman (r) and eta (h) CCC for univariate associations are also presented.…”
Section: Central Mechanisms Trait At Baseline As a Predictor Of Pain mentioning
confidence: 99%
“…Knee pain might either resolve or persist over time. Knee pain persistence after therapeutic intervention is weakly predicted by structural factors within the knee, including radiographic OA and ultrasound effusion 12 . Other characteristics have also been found to predict worse pain at follow up, particularly after surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, a recent study has shown that patients with extensive structural and joint damage from OA are less likely to respond to intraarticular steroid injections in the long term (> 6 months); however, in the short term, structural damage seems to have little effect on the efficacy of the injection. 13 Although the incidence of adverse effects is rare, intraarticular administration of glucocorticoids is not without inherent risk. Serial injections are often not recommended as it has been studied that long-term injections of intra-articular glucocorticoids may lead to greater structural damage and cartilage volume loss measured by magnetic resonance imaging (MRI).…”
Section: Intra-articular Injections Corticosteroidsmentioning
confidence: 99%